2020
DOI: 10.1074/jbc.ra120.013692
|View full text |Cite
|
Sign up to set email alerts
|

Prothrombin is a binding partner of the human receptor of advanced glycation end products

Abstract: The receptor for advanced glycation end products (RAGE) plays a key role in mammal physiology and in the etiology and progression of inflammatory and oxidative stress-based diseases. In adults, RAGE expression is normally high only in the lung where the protein concentrates in the basal membrane of alveolar Type I epithelial cells. In diseases, RAGE levels increase in the affected tissues and sustain chronic inflammation. RAGE exists as a membrane glycoprotein with an ectodomain, a transmembrane helix and a sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…It has been shown that ligand binding mainly occurs in the V-type domain ( 2 ). The V-shaped structure of its extracellular ligand binding part can bind to the Gla domain of prothrombin (F2) under normal physiological conditions ( 3 , 4 ). Under normal physiological conditions, the expression level of RAGE is low; however, due to the accumulation of RAGE ligands, the expression of RAGE is upregulated under inflammatory conditions ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that ligand binding mainly occurs in the V-type domain ( 2 ). The V-shaped structure of its extracellular ligand binding part can bind to the Gla domain of prothrombin (F2) under normal physiological conditions ( 3 , 4 ). Under normal physiological conditions, the expression level of RAGE is low; however, due to the accumulation of RAGE ligands, the expression of RAGE is upregulated under inflammatory conditions ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…RAGE is an MHC class III encoded protein belonging to the immunoglobulin (Ig) superfamily that was initially recognized as a receptor for advanced glycation end products (AGEs); however, it rapidly became revealed that this receptor has a multitude of ligands, including S100 proteins such as S100B, S100A4, S100A7, S100A8/A9, S100A11, S100A12, HMGB1, amyloid β peptide, prothrombin, chondroitin sulfate E, heparan sulfate, heparin and the complement C1q and C3a components [ 140 , 333 , 334 , 335 , 336 , 337 , 338 ]. Additional RAGE ligands include the neutrophil cationic antimicrobial protein CAP37 and the neutrophil proteases: CathG, NE and PR3 [ 227 , 238 , 339 ].…”
Section: Pro-tumor Function Of Ragementioning
confidence: 99%
“…Peptide mixtures were analyzed in duplicate by nano-LC-HRMS as described by Degani et al with few modifications in the multi-step separative gradient [26]. Briefly, for each sample, 5 µL of solubilized peptides in 0.1% TFA were injected onto the Acclaim PepMap C18 column (75 µm × 15 cm, 100 Å pore size), protected by a pre-column (Acclaim PepMap, 100 µm × 2 cm, 100 Å pore size), both from Thermo Scientific (Milan, Italy).…”
Section: Nano Hplc-hrms Analysismentioning
confidence: 99%